2015
DOI: 10.1002/chem.201501889
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Seven‐Membered Heterocycle, Containing B, C, N, O, and P Atoms, inside a Smaragdyrin Macrocycle

Abstract: Unprecedented examples of smaragdyrin macrocycles containing seven membered heterocyclic rings were synthesized under simple reaction conditions in high yields. The heterocycle formed inside smaragdyrin macrocycle is rare example of heterocycle containing five different atoms, such as B, C, N, O, and P atoms. The mixed B(III) and P(V) complexes of smaragdyrin macrocycles showed new structural, spectral, and electrochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The DFT‐optimized structure of 8 a (Figure a) indicated that it was a bicyclic spiro compound. Similarly to previous observations for the DFT structure of 6 a , we observed a deviation from planarity in the DFT structure of 8 a . However, in 8 a , the B III ion was very close to the meso ‐carbon plane with a small displacement of 0.049 Å (Table ).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The DFT‐optimized structure of 8 a (Figure a) indicated that it was a bicyclic spiro compound. Similarly to previous observations for the DFT structure of 6 a , we observed a deviation from planarity in the DFT structure of 8 a . However, in 8 a , the B III ion was very close to the meso ‐carbon plane with a small displacement of 0.049 Å (Table ).…”
Section: Resultssupporting
confidence: 87%
“…The average bond angles at the B III ion in 8 a were uniformly tetrahedral (109.5±1°); this ideal geometry led to a more‐stable compound. In contrast, the corresponding angles in 6 a were 109.38±4° . In addition, the B III −N2 and B III −N3 bond lengths were identical in 8 a , whereas a difference of 0.05 Å was observed in 6 a .…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations